“ARABISTS” AGAINST “LATINISTS”: THE LATINIZATION OF THE ALPHABET IN ADYGEA IN THE 1920s - Neflaseva, Naima Aminovna (History, Archeology and Ethnography of the Caucasus, 2022)
The purpose of the present article is to analyze the positions of the Muslim authority of Adygea in the course of implementing the policy of latinization in the Adyghe Autonomous Region in the 1920s. An analysis of the Soviet, modern Russian and western historiography of Soviet linguistic construction in the North Caucasus and Adygea, in particular, shows that this issue lies on the periphery of historical knowledge. The research methodology is based on the principles of historicism, objectivity and consistency. The semiotic approach has been productive for the analysis of the aspect under consideration. The research was carried out by methods of retrospective, comparative historical, logical and statistical analysis. The author notes that by the time of the Soviet language reform, the clergy was an authoritative social stratum, although it was rapidly losing its status and professional positions: there was a radical transformation of its roles in a secular and atheistic state. The reaction of the clergy and part of the Muslims of Adygea to the policy of the latinization of alphabet for the Western Circassians was expressed in organization the congress of Muslims and clergy in 1925 and the Women’s Religious Congress in 1928. Opposing the latinization, the elite of the Muslim authority, according to the author, not only fought for access to educational resources, but defended the basic sacred meanings of the Arabic script. Replacing the alphabet was seen by them as a cultural gap. The main conclusion is that the latinization of the alphabet and, in particular, its propaganda support became one of the means stigmatizing the Muslim intelligentsia and clergy as an obstacle to building a new Soviet society. Latin graphics and language reform became one of the tools to combat the influence of the Muslim clergy and displace the Muslim elites. The resource of influence of the most educated and authoritative clerics, potentially effective in the realization of social and educational projects of the young Soviet regime, turned out to be unclaimed.